Artificial Intelligence as an Innovative Solution in the World of Education - Angul, Angelina; Sogen, Maria Magdalena Beatrice; Boko, Heddy Mamida Yosefa; Belo, Ivonia Nazario Alves (JUPE : Jurnal Pendidikan Mandala, 2025)
The rapid advancement of digital technology has led to significant changes in the education sector, increasing the demand for responsive and efficient educational systems. Artificial Intelligence (AI) has emerged as an innovative alternative capable of enhancing effectiveness, personalization, and accessibility in learning. This article reviews the use of AI in education, including adaptive learning systems, educational chatbots, and virtual tutors, which create a more interactive learning experience tailored to the individual needs of each student. While AI offers numerous benefits, such as improved access to education in remote areas, issues related to ethics, data privacy, and infrastructure readiness must also be addressed. Utilizing a literature review method, this article connects the latest theories and practices regarding the implementation of AI in education and provides recommendations for efficient integration. Research findings indicate that AI has remarkable potential to transform education, fostering a more adaptive and responsive learning environment and preparing future generations to face the challenges of the times.Keywords: Artificial Intelligence (AI), Adaptive Learning Systems, Personalized Learning